Case report: Combined transcutaneous spinal cord stimulation and physical therapy on recovery of neurological function after spinal cord infarction - León, Felix; Rojas, Carlos; Aliseda, María José; del Río, Gerardo; Monzalvo, Eduardo; Pliego-Carrillo, Adriana; Figueroa, Jimena; Ibarra, Antonio; Lavrov, Igor; Cuellar, Carlos A. (Frontiers in Medicine, 2024)
The case of a 37-year-old woman who suffered from spinal cord infarction (SI), resulting in a complete spinal cord injury (AIS A, neurological level T10), and autonomic dysfunction is presented. This study aimed to assess the effect of transcutaneous Spinal Cord Electrical Stimulation (tSCS) on improving motor, sensory, and autonomic function after SI. During the first 8 months, tSCS was applied alone, then, physical therapy (PT) was included in the sessions (tSCS+PT), until completion of 20 months. Compared to baseline, at 20 months, an increase in ISNCSCI motor (50 vs. 57) and sensory scores (light touch, 72 vs. 82; pinprick, 71 vs. 92) were observed. Neurogenic Bladder Symptoms Score (NBSS) changed from 27 at baseline to 17 at 20 months. ISAFSCI scores in sacral autonomic function improved from 0 pts (absent function) to 1 pt. (altered function) indicating better sphincter control. EMG recordings during volitional movements, including overground stepping with 80% of body weight support showed activity in gluteus medialis, tensor fascia latae, sartorius, rectus femoris, biceps femoris, tibialis anterior, and gastrocnemius medialis, indicating a partial reversion of paralysis. RMS analysis indicated higher activity during “tSCS on” compared to “tSCS off” during overground stepping in bilateral rectus femoris (p < 0.001) and gastrocnemius medialis (p < 0.01); and unilateral biceps femoris, and tibialis anterior (p < 0.001). As this is the first report on the use of tSCS in the case of SI, future studies in a case series are warranted.